New insights into hallux valgus by whole exome sequencing study. Issue 14 (July 2021) - Jia, Jun; Li, Junyi; Qu, Huiqi; Li, Mengyu; Zhang, Sipeng; Hao, Jun; Gao, Xinyi; Meng, Xinyi; Sun, Yan; Hakonarson, Hakon; Zeng, Xiantie; Xia, Qianghua; et al.
The traditional view is that the occurrence and development of hallux valgus (HV) are mainly due to environmental factors. Recent studies have suggested the large contribution of genetic heritability to HV, but it remains elusive about the genetic variants underlying the development of HV. To gain knowledge about the molecular mechanisms of HV pathogenesis by genetic approach, whole exome sequencing studies were performed in 10 individuals (7 affected by HV and 3 unaffected) from three independent families. Specific mutations were found to be related to the pathogenesis of HV and conform to the laws of inheritance. A total of 36 genes with functional candidate single nucleotide variants were identified. Genetic predisposition plays an important role in the development of HV. Interestingly, some of these genes are related to chronic arthritis, such as the complement encoding gene C7, or are related to long toe or long fingers, such as TTN, COL6A3, LARS, FIG4, and CBS . This study identified rare potentially pathogenic mutations represented by genes related to digital anomalies and chronic arthritis underlying the familial types of HV, which acquired new insights into the genetic and physiological foundations of HV, thereby might improve accurate prevention and drug development for HV.